2019
DOI: 10.5194/bg-16-755-2019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-year effect of wetting on CH<sub>4</sub> flux at taiga–tundra boundary in northeastern Siberia deduced from stable isotope ratios of CH<sub>4</sub>

Abstract: Abstract. The response of CH4 emission from natural wetlands due to meteorological conditions is important because of its strong greenhouse effect. To understand the relationship between CH4 flux and wetting, we observed interannual variations in chamber CH4 flux, as well as the concentration, δ13C, and δD of dissolved CH4 during the summer from 2009 to 2013 at the taiga–tundra boundary in the vicinity of Chokurdakh (70∘37′ N, 147∘55′ E), located on the lowlands of the Indigirka River in northeastern Siberia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Normally, snowmelt and active layer thawing start in the late May through to early June; the growing season is from late June to early August. The average thaw depth observed between 3 July and 9 August at the study sites was 31±12 cm [65], whereas the maximum thaw depth was found at the end of thaw season (the first half of September). The active layer begins to freeze in the second half of September through to October and freezes completely between November and December.…”
Section: Methodsmentioning
confidence: 99%
“…Normally, snowmelt and active layer thawing start in the late May through to early June; the growing season is from late June to early August. The average thaw depth observed between 3 July and 9 August at the study sites was 31±12 cm [65], whereas the maximum thaw depth was found at the end of thaw season (the first half of September). The active layer begins to freeze in the second half of September through to October and freezes completely between November and December.…”
Section: Methodsmentioning
confidence: 99%
“…These low C emissions are speculated to partly be caused by the distinct cold and dry weather of Siberia which is located in Asian Russia Table 4 . from water-logged forests in Siberia Shingubara et al, 2019 ; this is particularly the case in western Siberia which features 52.4 million ha of wetland Glagolev et al, 2011;Terentieva et al, 2016 ; this is 0.12 times the emission Glagolev et al, 2011 .…”
Section: Boreal Forestsmentioning
confidence: 97%
“…However, they only observed less than two years of CH 4 fluxes and lacked interannual variations. Shigubara et al [66] found that soil thawing depth can partly explain the interannual variations of CH 4 flux in northeastern Siberia. Our results also showed that interannual variation of CH 4 fluxes may be controlled by the differences of maximum permafrost active layer thawing depths; however, more years of data are needed to confirm this conclusion.…”
Section: Effects Of Thawing On Annual Variations Of Ch 4 Fluxesmentioning
confidence: 99%